2021
DOI: 10.1038/s41419-021-03409-0
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo pathway component Wwc2 is a key regulator of embryonic development and angiogenesis in mice

Abstract: The WW-and-C2-domain-containing (WWC) protein family is involved in the regulation of cell differentiation, cell proliferation, and organ growth control. As upstream components of the Hippo signaling pathway, WWC proteins activate the Large tumor suppressor (LATS) kinase that in turn phosphorylates Yes-associated protein (YAP) and its paralog Transcriptional coactivator-with-PDZ-binding motif (TAZ) preventing their nuclear import and transcriptional activity. Inhibition of WWC expression leads to downregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 71 publications
3
12
0
Order By: Relevance
“…In contrast, WWC1 is primary expressed in epithelial cells. Moreover, recent studies showed that a WWC2 deletion results in severe defects in angiogenesis [ 34 ]. These data confirm our findings about WWC1 playing a subordinate role in angiogenesis, as it is of secondary importance for the most essential cell type of blood vessels, the ECs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, WWC1 is primary expressed in epithelial cells. Moreover, recent studies showed that a WWC2 deletion results in severe defects in angiogenesis [ 34 ]. These data confirm our findings about WWC1 playing a subordinate role in angiogenesis, as it is of secondary importance for the most essential cell type of blood vessels, the ECs.…”
Section: Discussionmentioning
confidence: 99%
“…Equally unknown is whether there is a tissue-specific difference in composition of Hippo signalling pathway. Recently, we have demonstrated that WWC2 protein plays an important role during embryonic and postnatal angiogenesis [ 34 ]. In this study, we analysed whether WWC2 is only important for retinal angiogenesis during development or also required for vascular maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Functional studies of the WWC2 gene can be performed by immunohistochemical analysis or western blot using antibodies against the WWC2 protein. WWC2 mRNA expression studies can be performed by various methods such as whole-mount in situ hybridization or quantitative reverse transcriptase polymerase chain reaction ( 34 , 35 ). In this study, we did not perform a functional study of the WWC2 gene since we did not have lung tissue samples obtained from deceased patients with PPHN and a mouse model with PPHN could not be created in our setting.…”
Section: Discussionmentioning
confidence: 99%
“…Length of hospital stay (days)22(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) In-hospital mortality2 (3.7) Data are presented as mean ± standard deviation, median (interquartile range), or n (%). PPHN, persistent pulmonary hypertension of the newborn.…”
mentioning
confidence: 99%
“…Cell lysate preparation and Western blotting analysis were performed as described earlier. 14 Briefly, confluent-grown cells from a 10 cm diameter plate or 15 mg snap-frozen human adult testicular tissue with CS (n = 1) were lysed using 500 μL IP buffer (1% Triton X-100, 20 mM Tris-HCl pH 7.4, 20 mM NaCl, 50 mM NaF, 15 mM Na 4 P 2 O 7 , 1 mM EDTA) containing phosphatase and protease inhibitor cocktails (P5726-5ML, P0044-5ML, P8340-1ML; Sigma Aldrich; 04693116001; Roche, Basel, Switzerland). Cells were scraped with a cell scraper and tissue was sheared with a small mortar.…”
Section: Western Blot Analysis Of Wwc2 In Cell and Tissue Lysatesmentioning
confidence: 99%